Монолитный балансный смеситель диапазона частот 80–100 ГГц - Aseeva, E. N; Mai, V. I.; Mai, A. V.; Superson, V. I.; Tkachenko, V. V. (PE "Politekhperiodika", Book and Journal Publishers, 2003)
A monolithic balanced mixer operating in the 80–100 GHz frequency range has been developed and studied. The device features a high level of integration and resistance to mechanical and climatic factors.